Alliance success factors and performance in social economy enterprises. Issue 5 (19th June 2017) - Bastida, Ramon; Marimon, Frederic; Tanganelli, David
Abstract : Purpose: Establishing alliances between social economy enterprises (SEEs) is considered to be a solution to the problem of providing enough resources and knowledge to compete in the global market and, at the same time, to maintain identity and ownership. Nevertheless, an important number of alliances breaks up after several years. Therefore, the purpose of this paper is to study the key factors that affect alliances' development and outcome. In this study, the success factors that have been extensively tested in investor-owned companies are assessed in SEEs, which present important differences in organizational issues and corporate principles and values. Design/methodology/approach: This study defines a scale that includes the most important factors that might be controlled by SEE managers to develop successful alliances. These factors are grouped into three categories: relational capital, relationship governance and the partner selection process. The study also assesses the impact of these factors on alliance performance. Findings: Statistical analysis through structural equation modelling shows that relationship governance and the partner selection process have a significant impact on performance. Therefore, they can be considered success factors in alliances among SEEs. Originality/value: Taking into account the relevant contribution of the SEEs to the European economy, and having noted the scarce number of studies about alliances success factors in the social economy sector, this study offers a significant contribution to this research field. Moreover, findings will be also interesting for SEE managers and social economy authorities when designing programmes to empower and support alliances.